2012
DOI: 10.1590/s1809-29502012000300010
|View full text |Cite
|
Sign up to set email alerts
|

Complicações e condutas fisioterapêuticas após cirurgia por câncer de mama: estudo retrospectivo

Abstract: RESUMO | Após cirurgia por câncer de mama, as mulheres estão sujeitas a desenvolver algumas complicações físicas. Os objetivos deste trabalho foram: investigar o desfecho dessas mulheres, que, durante o primeiro mês pós-operatório, foram submetidas a um programa de reabilitação e identificar ao longo de dois anos as complicações mais frequentes e as condutas fisioterapêuticas mais adotadas. Foi um estudo descritivo, retrospectivo, com dados de 707 prontuários de mulheres operadas por câncer de mama no Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
16

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 25 publications
0
8
0
16
Order By: Relevance
“…36,38 Other complications are frequently reported in association with lymphedema, such as restriction of ipsilateral should mobility in about 16.7% of women treated with breast cancer. 39 It has also been reported that the incidence of skeletal muscle complications is an age-related phenomenon, being higher in women over the age of 50 years submitted to lymphadenectomy. 40 Other reported morbidities related to breast cancer treatment are neuropathy, rotator cuff disease, adhesive capsulitis, postmastectomy pain syndrome, and intercostobrachial neuralgia.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…36,38 Other complications are frequently reported in association with lymphedema, such as restriction of ipsilateral should mobility in about 16.7% of women treated with breast cancer. 39 It has also been reported that the incidence of skeletal muscle complications is an age-related phenomenon, being higher in women over the age of 50 years submitted to lymphadenectomy. 40 Other reported morbidities related to breast cancer treatment are neuropathy, rotator cuff disease, adhesive capsulitis, postmastectomy pain syndrome, and intercostobrachial neuralgia.…”
Section: Discussionmentioning
confidence: 98%
“…There is considerable variation in the incidence, ranging from 3.5% to 44.8%, probably due to the diversity of methods used in making the diagnosis, and the fact that it is a time‐dependent phenomenon, with the RR increasing over time . Other complications are frequently reported in association with lymphedema, such as restriction of ipsilateral should mobility in about 16.7% of women treated with breast cancer . It has also been reported that the incidence of skeletal muscle complications is an age‐related phenomenon, being higher in women over the age of 50 years submitted to lymphadenectomy .…”
Section: Discussionmentioning
confidence: 99%
“…Esta dor geralmente está associada com a neoplasia devido à invasão ou a compressão das estruturas, devido ao tratamento que inclui a radioterapia, fibrose, neuropatia, quimioterapia e o pós-operatório 3 . A dor também pode estar associada à presença do dreno aspirativo 10 .…”
Section: Discussionunclassified
“…6 The main complications related to surgery are sensitivity impairment, seroma production, altered ventilatory capacity, lymphedema, axillary cording, reduced strength on the upper limb, reduced range of motion (ROM) of the arm and shoulder, and pain. 7,8 Pain itself is the main physical/functional impairment reported by patients, 9 with a prevalence of up to 60%. 9,10 Functionality involves the interrelation of the personal aspects of an individual (physical and emotional) with the surroundings (the environment and the engagement on activities).…”
Section: Introductionmentioning
confidence: 99%